Pengaruh Kuliah Online Terhadap Efektivitas Pembelajaran Mahasiswa Prodi Pendidikan Administrasi Perkantoran Di Universitas Negeri Jakarta - Julia Risky Handayani; Marsofiyati Marsofiyati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research is motivated by the development of increasingly sophisticated technology and the need for skills for students in facing an increasingly competitive world of work, however, several universities still use online learning methods which causes students to lack a deeper understanding of practical courses that suit their needs. working world. This research was conducted with the aim of analyzing the effect of online lectures on the learning effectiveness of students in the Office Administration Education Study Program at Jakarta State University, especially students of the class of 2022. The research method used was a quantitative approach with survey design, which involved distributing questionnaires to 41 students from class B Office Administration Education Study Program class of 2022 to be able to collect all data and information regarding their perceptions of online lectures and their impact on practicum-based learning activities, and this data was analyzed using SPSS version 29.0.2.0 (20). These findings also show that although online learning can run well, there are several obstacles that accompany it which reduce the effectiveness of learning, such as boredom and difficulty understanding the learning material. This research has important implications for educational institutions in improving the quality of teaching materials and teaching methods used during online learning in order to increase the effectiveness of learning in the future.